A Regional Approach Shows Differences Among Invasive Ants Solenopsis geminata and Wasmannia auropunctata (Hymenoptera: Formicidae) Within Its Native Range of Distribution. Issue 3 (17th June 2021) - Rojas, Patricia; Fragoso, Carlos
Abstract: Worldwide, two of the most harmful invasive ants typical of disturbed sites are Solenopsis geminata (Fabricius) and Wasmannia auropunctata (Roger). Both are natives of the Neotropics and are widely distributed all over the tropics. Within its original geographic range, there are few data on its abundance and potential damage to natural ecosystems. In this study, we recorded their abundance and relationships to diversity and richness of soil ant communities in two localities with different amount of forested area (López Mateos, LM 77% and Venustiano Carranza, VC 27%), at Los Tuxtlas reserve. In each locality, four land use systems (LUS) were sampled: tropical rain forests, agroforestry plantations, annual crops, and pastures. Data were gathered from 360 ant samples obtained from litter squares, pitfall traps, and soil monoliths in 40 sampling points (20 per locality, and five per LUS). Solenopsis geminata was more abundant in LM than in VC; the opposite trend was observed for W. auropunctata . In LM, S. geminata was more abundant in crops than in the other LUS, whereas W. auropunctata tended to have higher abundances in less managed sites of both localities. Abundance and species richness of ant communities were higher in LM than in VC. At regional and local levels, we found negative relationships between the abundance of S. geminata and species richness; the inverse pattern was found for W. auropunctata . We conclude that at Los Tuxtlas, W. auropunctata can be considered as a typical dominant native species, whereas S. geminata is the common exotic invasive ant.